Kebijakan Pemerintah Dalam Menangani Konflik Agraria Dan Keadilan Sosial - Tyaningrum, Annisa Mayang; Sudarsono, Sudarsono; Hadiyantina, Shinta (Bacarita Law Journal, 2025)
Government policy in dealing with agrarian conflicts in Indonesia is very important to achieve social justice. Agrarian conflicts often arise due to injustice in the control and use of natural resources, which has an impact on society, especially vulnerable groups. Based on the principles of Pancasila and the 1945 Constitution, the government has the responsibility to create prosperity for all people, including in terms of distribution of land and other resources. The government has implemented various strategies to overcome agrarian conflicts, including formulating inclusive and fair policies. In the context of public policy, social justice is the main basis. This includes protecting the rights of communities marginalized due to unfair development policies. An approach based on community participation in decision making is expected to reduce the negative impacts of these policies. In this way, the government not only functions as a regulator but also as a facilitator who creates an environment that supports social justice for all Indonesian people. This research uses normative legal research methods, using a case approach, a statutory approach and a conceptual approach. Overall, the success of government policies in dealing with agrarian conflicts and realizing social justice is highly dependent on a commitment to protecting people's rights and creating a just and transparent system. Implementation of the principles of social justice in every aspect of community life will be the key to achieving this goal. The aim of this research is to analyze the formulation of inclusive and socially just government policies regarding agrarian conflicts that occur in Indonesia.